Enhancement of crossflow ultrafiltration for the treatment of stabilized oily emulsions - Thaksina Poyai (2019)
© 2019, Chulalongkorn University, Faculty of Fine and Applied Arts. All rights reserved. Separation of stabilized oil droplets was conducted via crossflow ultrafiltration (UF) in a laboratory scale. A plate-and-frame membrane module was operated with two commercial organic membranes: Regenerated cellulose (RC) and polyethersulfone (PES). Cutting oil was used for preparing oil-in-water emulsions. Membrane fluxes were observed under varied oil concentrations and transmembrane pressures (TMP). It was found that UF provided oil rejection more than 97% for all operational cases. The optimal operating condition was found at the oil concentration less than 1 g/L and TMP of 2-3 bar. As predicted by Hermia’s model, the dominant fouling mechanism was the cake formation upon the membrane surface. The fouled membrane was effectively regenerated by the sequential cleaning of 0.5N-SDS, 0.1N-NaOH, and 0.01N-EDTA, respectively. The cleaned membrane was acquired with 96% flux recovery (FR) and 55% resistance removal (RR). Additionally, an integration of UF and pretreatments (i.e., chemical destabilization and coalescence) could improve flux decline of the membrane, while satisfactory discharge quality was achieved.